Histopathological And Biochemical Evaluation Of Piperine-Induced Changes In Ovarian Follicles And Hormonal Profile In Adult Albino Rats - Mir, Urfa Zaryab; Mahmood, Amna; Ejaz, Rabia; Aslam, Amna; Mansoor, Saqib; Javed, Muhammad (Journal of Rawalpindi Medical College, 2026)
Objective: This study aimed to evaluate histopathological and biochemical alterations caused by Piperine on the ovaries of adult female Wistar albino rats. Methods: Thirty rats (3–4 months old, 200–250 g) were divided into three groups (n=10 each). Group A (control) received normal saline, Group B received Piperine at 5 mg/kg, and Group C received Piperine at 10 mg/kg body weight daily for 30 days. Serum estrogen and progesterone were measured using ELISA. Histology of ovarian tissues was done, and estrous cycle changes were monitored. Results: Piperine exposure produced a dose-dependent increase in secondary follicle diameter (Group A: 210.4 ± 15.2 µm; Group B: 285.7 ± 18.9 µm; Group C: 342.1 ± 22.7 µm; p < 0.001). Serum estrogen was significantly elevated in Groups B and C (62.7 ± 5.3 pg/ml and 75.4 ± 6.1 pg/ml) compared to controls (48.2 ± 4.5 pg/ml), while progesterone declined (Group A: 1.45 ± 0.35 ng/ml; Group B: 1.01 ± 0.33 ng/ml; Group C: 0.41 ± 0.12 ng/ml; p < 0.001). Conclusion: Piperine caused dose-dependent enlargement of secondary follicles with elevated estrogen and reduced progesterone, leading to arrest of the ovarian cycle at the proestrus stage. These findings suggest potential reproductive toxicity of piperine in females of reproductive age. Keywords: Piperine, Secondary Follicles, Estrogen, Progesterone, Estrous cycle.